Testing Taxonomies: Beyond Card Sorting. Issue 5 (3rd August 2015) - Soranzo, Alberta; Cooksey, Dave
<x xml:space="preserve">Abstract</x> EDITOR'S SUMMARY Whether created by user experience designers or information specialists, taxonomies should always be subjected to evaluation processes. The taxonomy's terms and relationships must be assessed in the context of its implementation as part of information architecture. Traditional card sorting in a face‐to‐face setting can be performed by any number of testers working independently; delphi‐method card sorting involves iterative review by a succession of testers. Each requires advance preparation of cards showing candidate terms to be arranged in a way that makes sense to each tester. Dialogue with testers during the process provides qualitative insight into their thinking and logic, and data analysis sheds light on users' mental models of the taxonomy. Usability studies then reveal how testers use the taxonomy to navigate, search and tag content. With similar preparation, online sorting methods facilitate testing and provide rich results for analysis. Regardless of the method used, testers should be selected with care, and terms must be distinguished from navigation and context. Testing should be performed early, using small studies to focus on key areas and larger samples for quantitative analysis.